Effect of Soil Erosion on Europe's Crop Yields - Bakker, Martha M; Govers, Gerard; Jones, Robert A; Rounsevell, Mark D. A (Ecosystems (New York), 2007)
Soil erosion negatively affects crop yields and may have contributed to the collapse of ancient civilizations. Whether erosion may have such an impact on modern societies as well, is subject to debate. In this paper we quantify the relationship between crop yields and soil water available to plants, the most important yield-determining factor affected by erosion, at the European scale. Using information on the spatial distribution of erosion rates we calculate the potential threat of erosion-induced productivity losses. We show that future reductions in productivity in Europe as a whole are relatively small and do not pose a substantial threat to crop production within the coming century. However, within Europe there is considerable variability, and although productivity in northern Europe is not likely to be significantly reduced by soil erosion, for the southern countries the threat of erosion-induced productivity declines is stronger.